2020
DOI: 10.18632/aging.102928
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognosis analysis of TET family in acute myeloid leukemia

Abstract: TET family members (TETs) encode proteins that represent crucial factors in the active DNA demethylation pathway. Evidence has proved that TET2 mutation is associated with leukemogenesis, drug response, and prognosis in acute myeloid leukemia (AML). However, few studies revealed the TETs expression and its clinical significance in AML. We conducted a detailed expression and prognosis analysis of TETs expression in human AML cell lines and patients by using public databases. We observed that TETs expression esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
2
22
0
1
Order By: Relevance
“…This heterogeneity in 5-hmC levels may be due to either compensation of TET2-deficiency by up-modulation of TET3 or by factors other than mutations which influence 5-hmC in WT cases, as previously reported. 33 Our results indicate that elevated TET3 levels compensated TET2-deficiency in terms of clinical outcomes in both univariate and multivariate settings (Fig. 2F-G, TableS2-3).…”
Section: Resultssupporting
confidence: 53%
“…This heterogeneity in 5-hmC levels may be due to either compensation of TET2-deficiency by up-modulation of TET3 or by factors other than mutations which influence 5-hmC in WT cases, as previously reported. 33 Our results indicate that elevated TET3 levels compensated TET2-deficiency in terms of clinical outcomes in both univariate and multivariate settings (Fig. 2F-G, TableS2-3).…”
Section: Resultssupporting
confidence: 53%
“…in vitro 91 high expression of TET3 may be in cell culture 53,92 a positive prognostic marker. 97 in vitro 71 correlated with adverse outcome in cell culture 70 in male AML patients. Mutations in KDM6A associated with cytarabine resistance.…”
Section: Context 1 Heterozygous Mutations In Tet2mentioning
confidence: 92%
“…These molecules are intermediates in the pathway of in vitro 51,91 and in MLL-rearranged leukemia 96 . cell culture 50,51,53,[92][93][94] Reduced expression in AML 97 Increased expression in MLL-rearranged leukemia 96 TET2 KIAA1546, Nbla00191 Methylcytosine 5mC, 5hmC and 5fC Increased activity Tumor suppressor in AML, MDS, dioxygenase TET2…”
Section: Context 1 Heterozygous Mutations In Tet2mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, higher expression of TET1 at diagnosis was associated with poor clinical outcomes in a cohort of 360 CN-AML patients [ 43 ]. Finally, a recent study demonstrated that high TET3 expression was an independent factor for better OS and disease-free survival (DFS) in AML [ 44 ]. Of note, patients with lower TET3 expression undergoing hematopoietic stem cell transplant (HSCT) showed better OS and DFS than those who did not proceed to HSCT [ 44 ].…”
Section: The Metabolomics Of Tet Family Of Genesmentioning
confidence: 99%